Проблемы стратегического планирования президентской избирательной кампании - Петров, О.; Полторак, В. (Социология: теория, методы, маркетинг, 1999)
There have been discussed the aspects of participation of Ukrainian specialists dealing with election technologies, first of all — experts in sociology and politicalsciences, in large-scale election campaigns like the Presidential ones, the problems related to the developing market of election services in the country, and specific attitude of Ukrainian politicians to the mentioned specialists. Analyzing one of such the Presidential election strategies, the authors have described the certain ways (adapted to Ukrainian conditions) of how to develop the main strategic line of election campaign, to determine the key problem, goal and tasks of election campaign, to reveal the ‘aim’ groups and use them, and others.